Are pregnancy support belts effective in treating pregnancy‐associated lumbopelvic pain?. Issue 4 (April 2017) - Phillips, James D.; Lew, Daniel B.
Abstract : EVIDENCE‐BASED ANSWER : Pregnancy support belts may decrease pelvic girdle and low back pain (SOR: C, systematic reviews of low‐quality RCTs). Flexible belts and rigid belts are associated with reduced symphyseal pain and appear to be equivalent. Flexible belts may be better tolerated than rigid belts (SOR: C, single low‐quality RCT without placebo control).